2009
DOI: 10.1007/s00125-009-1635-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of glucagon secretion in mouse and human pancreatic alpha cells by protein kinase C (PKC) involves intracellular trafficking of PKCα and PKCδ

Abstract: Aims/hypothesis Protein kinase C (PKC) regulates exocytosis in various secretory cells. Here we studied intracellular translocation of the PKC isoenzymes PKCα and PKCδ, and investigated how activation of PKC influences glucagon secretion in mouse and human pancreatic alpha cells. Methods Glucagon release from intact islets was measured in static incubations, and the amounts released were determined by RIA. Exocytosis was monitored as increases in membrane capacitance using the patch-clamp technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Another study [18] and we, here, have reported GLP-1 values in the picomolar range, suggesting intrinsic islet biological variability and/or differences in experimental conditions. In addition, in our study, glucagon release from isolated islets was similar to that reported by some other authors [36,37], but several fold lower than that observed during perifusion experiments [38]. All this led, in our hands, to a glucagon/GLP-1 molar secretion ratio (basal condition) of approximately 5.7, similar to findings previously reported for αTC1-6 cells [16].…”
Section: Discussionsupporting
confidence: 92%
“…Another study [18] and we, here, have reported GLP-1 values in the picomolar range, suggesting intrinsic islet biological variability and/or differences in experimental conditions. In addition, in our study, glucagon release from isolated islets was similar to that reported by some other authors [36,37], but several fold lower than that observed during perifusion experiments [38]. All this led, in our hands, to a glucagon/GLP-1 molar secretion ratio (basal condition) of approximately 5.7, similar to findings previously reported for αTC1-6 cells [16].…”
Section: Discussionsupporting
confidence: 92%
“…However, recent accumulating evidence suggests that dysregulation of glucagon secretion can also induce hyperglycemia, which is ameliorated by inhibition of glucagon function (6 -9). Moreover, it was reported that treatment with high glucose increased glucagon secretion from isolated islets and PKC is involved in this event, although the responsible PKC isozyme was not identified (12)(13)(14). Our data demonstrate that PKCδ signaling is responsible for the PMA-induced augmentation of glucagon secretion in the isolated islets.…”
Section: Discussionmentioning
confidence: 55%
“…Munc-18 has been implicated in transport of syntaxin 1A [32] and demonstrated to be phosphorylated by PKC [10]. More detailed studies are indeed needed in the future to be able to fully answer the question regarding syntaxin 1A trafficking in the alpha-cells but we have earlier shown that PKC plays an important role in the regulation of the pancreatic alpha-cell exocytosis [7].…”
Section: Discussionmentioning
confidence: 98%
“…In these experiments exocytosis was elicited by a train of ten 500 msdepolarisations from -70 mV to 0 mV (Fig 2a-b). It has earlier been suggested that the capacitance increase evoked by the two first and latter eight depolarisations of a train represent the maximum size of the RRP and the refilling from RP, respectively [7]. We used this approach and applied an antibody against SNAP-25 intracellularly by inclusion in the pipette solution.…”
Section: Antibodies Against Snap-25 Reduce Exocytosis Of Glucagon-conmentioning
confidence: 99%